2023
DOI: 10.3390/s23177435
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Medical Things and Healthcare 4.0: Trends, Requirements, Challenges, and Research Directions

Manar Osama,
Abdelhamied A. Ateya,
Mohammed S. Sayed
et al.

Abstract: Healthcare 4.0 is a recent e-health paradigm associated with the concept of Industry 4.0. It provides approaches to achieving precision medicine that delivers healthcare services based on the patient’s characteristics. Moreover, Healthcare 4.0 enables telemedicine, including telesurgery, early predictions, and diagnosis of diseases. This represents an important paradigm for modern societies, especially with the current situation of pandemics. The release of the fifth-generation cellular system (5G), the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 100 publications
0
20
0
3
Order By: Relevance
“…Ensuring that AI's diagnostic capabilities align with the highest standards is crucial to prevent unnecessary stress or missed diagnoses for patients ( El Zoghbi et al, 2023 ). The strategies to enhance patient care through AI integration reflect a growing consensus that AI can streamline routine tasks, allowing healthcare professionals to focus on personalized, patient-centered care ( Osama et al, 2023 ; Zarella et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring that AI's diagnostic capabilities align with the highest standards is crucial to prevent unnecessary stress or missed diagnoses for patients ( El Zoghbi et al, 2023 ). The strategies to enhance patient care through AI integration reflect a growing consensus that AI can streamline routine tasks, allowing healthcare professionals to focus on personalized, patient-centered care ( Osama et al, 2023 ; Zarella et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In multi-disciplinary healthcare settings, such as cancer treatment teams or trauma centers, this can significantly improve the quality of care. Specialists can simultaneously review patient records, diagnostic images, and test results, leading to well-informed treatment decisions and improved patient outcomes [ 7 ].…”
Section: Reviewmentioning
confidence: 99%
“…Healthcare professionals should be well-informed about these regulations to ensure their practices align with legal requirements. Compliance not only helps protect patient data but also mitigates the risk of legal repercussions [ 7 ].…”
Section: Reviewmentioning
confidence: 99%
“… 14 , 15 The Internet of Things (IoT) is an industrial tide that involves computers, the Internet, and communication networks and is a vital part of healthcare 4.0. 16 Recently, IoT technologies have included many features, such as continuous evaluation, real-time data transmission, personalized treatment, and remote care, which provide a new alternative for homebound COPD patients. 17 Park et al 18 reported that exercise capacity and quality of life can be improved by including a mobile health care app and IoT wearable devices.…”
Section: Introductionmentioning
confidence: 99%